Suitability of bioengineering channels in erosion control: Application to urban stormwater drainage systems - Muhammad, M.M. (Pushpa Publishing House, 2016)
This study assesses the hydraulic suitability of Turf Reinforcements Mat (TRM) and Erosion Control Blanket (ECB) as bioengineering materials for erosion control. Two different trapezoidal test channels were constructed for testing the biomaterials, in which one is narrow and non-uniform in cross section and the other one is regular in shape. Hydraulic characteristics of flow through these materials were determined in terms of flow velocities and shear stresses. The results obtained in all cases of flow depths show that the maximum velocity for TRM ranges between 0.23 to 0.86m/s, while that of ECB varies from 0.23 to 0.97m/s. Also, both TRM and ECB have shear stresses ranging from 0.766N/m2 to 3.372N/m2 including bed and bank shear stresses of the test channels. Furthermore, the greater the flow depth, the higher the velocities and shear stresses, except in the case of the regular channel when the flow depth is equal to 0.25m, the velocity suddenly dropped. However, lower flow depths gave velocities and shear stresses that are within the allowable values and appropriate for designing a stable channel. It was concluded that TRM performed the best for having lower velocity range and higher shear stresses compared to ECB. Â© 2016 Pushpa Publishing House, Allahabad, India.